Sedimentary evolution of Quaternary tufas and travertines (Tetouan-Northern Morocco): implications for earth processes and depositional systems. - Guerreiro, P. (2016)
The continental carbonates, such as travertine and tufa, are among the sediments recording climate change manly during Quaternary times. Their lithofacies and petrofacies are useful for understanding the related hydrologic, geomorphologic and climatic processes as well as the depositional palaeoenvironments. Thus, the present work deal with the analysis and interpretation of the main facies association of Tetouan city travertine cliffs and terraces. According to morphologic, sedimentologic and petrographic investigations coupled with 1/5000 scale mapping, four main facies associations were recognized and show from the top to bottom: i) barrage and cascade limestones, ii) base of the cascade limestone breccias and blocks, iii) lacustrine detrital deposits and iv) carbonate pedogenic crusts. The barrage facies associationis characterized by carbonate deposits with a wide textural features: a) massive micritic limestone, b) brecciated limestone with remnants of calcified leaves, stems of macrophytes and fresh-water gastropods, c) thin-layered calcite sheets (probably corresponding to ancient algal mats) or calcite layers to remnants of herbaceous plants, d) soft black pocket marls with remnants of calcified leaves, stems and mollusks (i.e. terrestrial and fresh-water gastropods). The base of the cascade facies association, located at the east and the central part of the escarpment, is made of fallen blocks detached from the carbonate build-up that constitutes the dam that are embedded in multi-colored crystalline travertine bands. The third facies association is constituted by detrital sediment strata with an obvious contribution from barrage and cascade limestones mainly supplied from the Dorsal calcaire relieves mainly made of calcacareous plateform deposits The fourth facies association correspond mainly to pedogenic carbonate crusts usually topping outcrops of lacustrine sediments, but also present in erosive surfaces or within cascade limestones. Vertical NNE-SSW fracture sets are found in the Oued Martil slope, fulfilled by carbonate crust-like material. Tetouan travertine petrofacies are mainly represented by: i) rolled crusts made of different morphological types: cylindrical, oncholites, flat and corrugated crystallized around various nucleus. ii) detrital fine to medium grained calcareous sands, iii) homogenous micritic facies with primary precipitation of micrite during periods of low flow velocities and calm waters and probably in relation to microbial activities, iv) micrite-coarse banded crystalline sheets consist of palisade calcite crystals related to cyclic changes in chemical, physical and/or environmental conditions or even diurnal cycles of microbial activity. In addition, this study has highlighted that Tetouan travertines may have formed under strong hydrodynamic environments within rapid water flow waterfalls intercalated with slower flow and calm waters periods. These travertines may also record the occurrence of seasonal climatic variations related to microclimatic fluctuation during part of the Holocene. In Southern Portugal the same type of Holocene terrestrial carbonate deposits, exhibit similarities in the petrofacies observed and in the facies association. A smaller urban coverage allows a detailed observation of the outcrops showing the existence of active and fossil incrusting systems fed by the Jurassic aquifers.